Measurement of the radiation level dose to patient from fluoroscopy device during cardiac catheterization - Luma Naji; Susan Zwyea; Alyaa Raheem (Journal of Techniques)
Fluoroscopy is a type of medical imaging that shows a continuous X-ray image on a screen, it is used in a wide range of examination and procedures for diagnosis such as in cardiac catheterization. Fluoroscopy can result in relatively high radiation doses, especially for complex interventional procedures that it needed to monitor radiation to reduce exposure. The purpose of this study is to determine the radiation doses for patients during cardiac catheterization exam and compare it with the permissible dose limits. The main parameters which are studied in this work are the time of exposure dose rate, x-ray techniques (milliamper. second), tube voltage (kilovolt) and Dose Area Product (DAP). Twenty-seven patients were included and  absorbed doses were measured and distributed according to Fluoroscopy (Fluo) time, mAs and Dose Area Product (DPA). It was found that the absorbed dose received by the patients has a  linear relationship with the Fluoroscopy time, mAs and DAP. Exposure dose rates were measured and compared with the maximum permissible dose (100 mGy/min), the estimated patient dose rate varied from (12-81.6) mGy/min) for 24 patients as a permissible dose in the safe side, and 3 patients exposed to higher values of the exposure dose rates ) over permissible dose) range (107.4-108) mGy/min